Patent analysis provides insights into the history of cotton molecular breeding worldwide over the last 50 years - Wei HE; Hui-min ZHAO; Xiao-wei YANG; Rui ZHANG; Jing-jing WANG (Journal of Integrative Agriculture, 2019)
Cotton is a globally important natural fiber and oilseed crop of crucial economic significance. Molecular breeding has become a dominant method of cotton cultivation because it allows for a shorter breeding period and directional selection of high quality genes. Patent data are key resources and are the core competitiveness of agricultural development, as the world's largest and most reliable source of technical information. However, little attention has been paid to patent analysis of cotton molecular breeding. This study uses bibliometric analysis methodology and technical classification indexing to reveal global development trends of cotton molecular breeding, based on patents by retrieval methods and expert screening. The annual number of patents, the life-cycle of patent-based technology, patent portfolios of primary countries, and main patentees, as well as technical distribution of patents, were analyzed in this study. In addition, this study put emphasis on the comparative analysis of two important patentees through patent roadmaps based on the relationship among patent citations. Finally, in order to understand the trend of new molecular breeding technology, patents related to clustered regularly interspaced short palindromic repeats (CRISPR), RNA interference (RNAi), and gene chip were also analyzed, all of which apply to cotton but also to other crops. Results in this paper can provide references for cotton molecular breeding researchers and relevant management departments.